Controversies in the TNM staging system for colorectal cancer - Samornmas Kanngurn (Journal of Health Science and Medical Research (JHSMR), 2010)
The stages of many cancers including colorectal cancer. One advantage of the TNM staging system is that it is revised continuously by the American Joint Committee of Cancer (AJCC) and the International Union Against Cancer (UICC) based on new evidence as it becomes available. The system still has some deficiencies and is being continually tested for the relevance of any questionable practices. Partial modification or even the complete change of some definitions are to be expected as such revisions continue. The goal is to minimize doubt that could lead to inappropriate treatment in patients from either underestimation or overestimation of cancer stages.